Examining Generation Z Loyalty in Medan's Fashion Sector Omnichannel - Pasaribu, Romindo M; Lubis, Arlina Nurbaity; Rini, Endang Sulistya; Sembiring, Beby Karina F (Journal of Ecohumanism, 2024)
Generation Z's mobile behavior is a challenge for retailers in the fashion industry to provide and create experiences and engagement that will ultimately form loyalty. create experiences and engagement that will ultimately form customer loyalty. customers. The purpose of this study is to examine and analyze experience, customer engagement, and hedonic cultural value orientation in increasing the loyalty of generation Z customers in Medan City. This research was conducted on Generation Z in Medan City with a sample size of 440 respondents. Data analysis technique data analysis technique using SEM PLS. The results show channel integration, customer experience experience, and customer engagement have a positive and significant effect on customer loyalty variables directly and indirectly. Experience and customer engagement mediate between channel integration and customer loyalty. customer loyalty. Hedonic cultural value orientation is able to strengthen the effect of customer engagement on loyalty but is unable to strengthen the relationship between customer experience and customer loyalty. customer experience and customer loyalty. This research confirms that fashion product retailers should use multiple channels, online and offline, that are well integrated into creating the customer experience. and offline channels that are well integrated in creating customer experience and customer engagement. Information delivered across all channels should be consistent to create a seamless shopping experience online. seamless shopping experience online. Retailers should engage customers by improving communication and providing entertaining services in the form of gamification. Gamification services can create a hedonic culture for Generation Z customers.